Learning English language on social media - Sattarova Saodat Narzullayevna; Baxriddinova Rushana Bahodir qizi (Zien Journals, 2021)
Today social media has become part and parcel of adults’ lives. Adult learners use social media much as a key to learn and improve their English as a foreign language (EFL) in academics. Currently, English instructors also encourage their adult learners within the realm of technologies. These students are very keen to use social media to learn English. Social media is for both teachers and educators in the process of texting, chatting and communicating with friends, family and the global community on Facebook, WhatsApp, Blogs, Wikis, LinkedIn, YouTube, Twitter, Telegram, Hangout and Snapchat simplifies and improves the process.
Keywords: Social media; EFL learners; Communicative practice; Application Programming